First Fossil of Rhinoclemmys Fitzinger, 1826 (Cryptodira, Geoemydidae) East of the Andes (2019)
We describe the first undisputable fossil of Rhinoclemmys (Cryptodira, Geoemydidae) east of the Andes, represented by an isolated nuchal bone found in one of the most important paleontological sites with association of fauna and humans (Muaco site, western Venezuela) from the Late Pleistocene of the southern Caribbean. The nuchal is complete and slightly wider (4.8 cm) than long (4.2 cm), preserving well-defined sulci of the cervical, vertebral 1, marginal 1, and pleural 1. Comparisons with extant and fossil specimens of Rhinoclemmys allow us to attribute this nuchal to Rhinoclemmys, albeit as an indeterminate species. The occurrence of Rhinoclemmys in the southern Paraguaná Peninsula indicates that during the Late Pleistocene this region had environmental conditions that allowed the survival of these freshwater-terrestrially adapted reptiles, particularly of 'paleo-springs' inside a semi-arid region. © 2019 Brazilian Society of Herpetology.